Introduction: The Varieties of Enactivism. - Ward, Dave; Silverman, David; Villalobos, Mario (Topoi: An International Review of Philosophy, 2017)
An introduction is presented in which the editors focus on the enactivist theoretical landscape, the enactive cognitive scientific approach to the study of the mind, and cognition.